Field assessment of insecticide dusting and bait station treatment impact against rodent flea and house flea species in the Madagascar plague context. - Adélaïde Miarinjara; Soanandrasana Rahelinirina; Nadia Lova Razafimahatratra; Romain Girod; Minoarisoa Rajerison; Sebastien Boyer (Public Library of Science (PLoS), 2019)
Bubonic is the most prevalent plague form in Madagascar. Indoor ground application of insecticide dust is the conventional method used to control potentially infected rodent fleas that transmit the plague bacterium from rodents to humans. The use of bait stations is an alternative approach for vector control during plague epidemics, as well as a preventive control method during non-epidemic seasons. Bait stations have many advantages, principally by reducing the amount of insecticide used, lowering the cost of the treatment and minimizing insecticide exposure in the environment. A previous study reported promising results on controlling simultaneously the reservoir and vectors, when slow-acting rodenticide was incorporated in bait stations called "Boîtes de Kartman". However, little evidence of an effective control of the fleas prior to the elimination of rodents was found. In this study, we evaluated bait stations containing insecticide powder and non-toxic attractive rodent bait for their potential to control rat fleas. Its efficacy was compared to the standard method. The impact of both methods on indoor and outdoor rodent fleas, as well as the human household flea Pulex irritans were analyzed at different time points after treatments. Bait stations did not cause any significant immediate or delayed reduction of rat fleas and increasing the number of operational bait stations per household did not significantly improve their efficacy. Insecticide ground dusting appeared to be the most efficient method to control indoor rat fleas. Both methods appeared to have little impact on the density of outdoor rat fleas and human fleas. These results demonstrate limited effectiveness for bait stations and encourage the maintenance of insecticide dusting as a first-line control strategy in case of epidemic emergence of plague, when immediate effect on rodent fleas is needed. Recommendations are given to improve the efficacy of the bait station method.